Implications Of Electronic Integrated Mortgage Rights Registration If The Guarantee Owner Dies - Happylenia Prasetya, Christina; Jamin, Mohammad; Saptanti, Noor (CV. Inara, 2024)
Service public-based technology from the Mortgage Rights system electronic expected can give convenience for user system that, will but in its implementation Not yet walk in a way maximum. Problems arise if the owner guarantee dies during the mortgage​​ in a way electronically registered. This Study’s objective is to know the implications of Integrated Mortgage Rights registration​ in a way electronically if the owner guarantee dies. Study This is study law normative. Data used in the study This is secondary data. Collected data is then analyzed in a way descriptive qualitative with the use statute approach or approach legislation. Research results this if the owner guarantee died when the Mortgage Rights were registered in a way electronics, cause Number Identity Population owner guarantee in system Registration of Mortgage Rights No registered. This matter is causing mortgage rights not to be born. Because the creditor​ did not get guarantee certainty law when the Deed Granting Mortgage Rights was already signed through a power of attorney to impose mortgage rights because the APHT cannot registered to the Land Office.